Senior High School Students' Scientific Habits of Mind Profile on Chemical Equilibrium: Case of Health and Environmental Topics - Pratama, Faiz Ilham; Rohaeti, Eli; Laksono, Endang Widjajanti (Jurnal Pendidikan Matematika dan Sains, 2024)
The rapid development of science and technology is a challenge for the era of disruption in the 21st century. These phenomena cannot be separated from the hard work of scientists who have scientific habits of mind (SHOM). Science learning that focuses on SHOM can be indicated by the scientific attitude of students during learning, so the benefits of SHOM are to bring out scientific attitudes in students. In addition, SHOM needs to be taught to students so they can solve problems in a structured and systematic way. This study aims to describe the SHOM profile of high school students on chemical equilibrium with the topic of health and the environment. This research includes quantitative descriptive research. The number of samples from this study was 80 students taken from one of the high schools in Magelang City. The data collection technique in this study was a questionnaire. The data research instrument used was a student questionnaire sheet which was a closed questionnaire with five choices namely SD (Strongly Disagree), D (Disagree), QA (Quite Agree), A (Agree), and SA (Strongly Agree). The number of statements that students have to answer is 25 items with details of 14 statements with positive meaning and 11 statements with negative meaning. Then, the data were analyzed by ideal criteria assessment The results of the research that has been done can be seen that the SHOM profile on chemical equilibrium material is 66.7427%. These results indicate that the students' SHOM profile on chemical equilibrium material is classified as fair. So learning modifications are needed such as modification of learning activities, use of learning models and strategies that encourage students to think scientifically, as well as selection of appropriate learning media in order to improve scientific habits of mind.